Aging Gracefully in Place: An Evaluation of the Capability of the CAPABLE© Approach. (March 2022) - Breysse, Jill; Dixon, Sherry; Wilson, Jonathan; Szanton, Sarah
As American adults live longer, society must prioritize effective strategies promoting safe aging-in-place and decreasing institutional health care costs. Social determinants of health, especially housing, critically influence older adult health, particularly for disadvantaged, low-income older adults. Johns Hopkins University developed Community Aging in Place—Advancing Better Living for Elders (CAPABLE © ), a client-centered, home-based program to improve older adults' function and capacity to age in place. This evaluation studied CAPABLE's long-term effectiveness in four distinct locations in California, North Carolina, Pennsylvania, and Vermont. Seven months after CAPABLE, intervention group participants experienced greater improvements than the control group in activities of daily living limitations (2-point vs. 0.7-point improvement, p = .012), falls efficacy (8.9-point improvement vs. 0.1-point worsening, p = .012), depression (1.3-point improvement vs. 0.4-point worsening, p = .021), and pain (1.5-point improvement vs. 0.3-point worsening, p = .002). These results add to existing research on short-term effectiveness in urban locales, showing CAPABLE yields long-term health improvement for older adults in micropolitan and small urban locations, with different implementation organizations, housing stocks, and clients.